Investment Spikes and Firm Profitability - Ogbonnia, ANUSI, Albert; Maryann, IGBODIKA, N.; Ikenna, EGUNGWU, (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Investment has become a window for enhancing firm profitability and other corporate objectives. This study aimed to investigate the effect of investment spike on the profitability of consumer goods firms quoted on the Nigerian Exchange Group between 2011 to 2021. The incidence of investment spike and size of investment spike were the independent variables controlled by the firm size while return on asset was the measure for firm profitability. Data were collected from the annual reports of the selected consumer goods firms. The study employed the pane regressed based on Fixed and Random Effect for data analysis. The results showed that all the variables of investment spike including incidence of spike and size of spike had positive and significant effects on the return on assets of consumer goods firms. The coefficient of determination and f-statistics revealed that revealed that investment spikes explained about 80% of variations in the firm profitability. The study posited that investment spike is a determinant of firm profitability among the consumer goods sector in Nigeria.